PENGARUH SARAPAN PAGI TERHADAP KONSENTRASI BELAJAR SISWA KELAS V DI SDS TARBIYATUL ISLAM SAMBAS TAHUN PELAJARAN 2023-2024 - Klania Istiqomah; Parni, Astaman (ADISAM PUBLISHER, 2024)
This journal aims to obtain complete and in-depth information about breakfast and concentration and the influence that exists between breakfast and student learning concentration at SDS Tarbiyatul Islam Sambas for the 2023-2024 academic year. The research approach used is quantitative with an associative type of research.The population is 28 people. The data analysis technique uses Pearson product moment correlation and simple linear regression, with the research results being that variable X breakfast is in the